Magnetic susceptibilities of dilute alloys of manganese and iron in magnesium and aluminum. - Treuil, Mireille. (University of Ottawa (Canada), 1960)
The ionic and electronic contributions to the total magnetic susceptibility of a non ferromagnetic metal alloy are discussed, and a review of the experimental techniques for measuring susceptibilities is given. The presence of even small amounts of ferromagnetic impurities can have disastrous effects on the measured susceptibilities, and a method is described for correcting for such impurities when the Gouy method is used. This enabled the true susceptibility of the non ferromagnetic part of a substance to be determined with an accuracy of .1% relative to Ge. The room temperature values of magnetic susceptibility of the dilute alloys of Mn and Fe in Mg and Al were measured in view of obtaining information about the electronic configuration of the transition elements in solution. A localized d electron picture rather than a d band picture was found to be adequate. The measured effective Bohr magneton numbers yielded two possible electronic configurations for the solute atoms. The possibility of distinguishing between these is discussed in terms of the corresponding change in population of the conduction band and its influence on the electronic susceptibility.
Keywords: Physics, Electricity and Magnetism.